L2 multiple-documents comprehension: Exploring the contributions of L1 reading ability and strategic processing. (August 2015) - Karimi, Mohammad Nabi
Abstract: There is much prior L2 research estimating the contributions of strategic processing and L1 reading ability to L2 reading comprehension. This line of inquiry has, however, been mainly followed in relation to single-text reading. While multiple-documents comprehension constitutes the bulk of what EFL/ESL students do in their current academic environments, L2 research investigating the contributions of these two variables to this type of comprehension in essentially lacking. Against this background, the present paper reports on a study examining the relative contributions of strategic processing and L1 reading ability to L2 single-text vs. multiple-texts comprehension. To this end, 114 EFL students took measures of L1 reading ability, L2 single-text and multiple-texts reading comprehension, as well as self-reported strategic processing. Data were analyzed using regression analyses. The results indicated that while L1 reading ability and strategic processing contributed significantly to L2 single-text reading, only strategic processing was shown to contribute to L2 multiple-texts reading. Strategic processing was also shown to account for a much larger proportion of variance in L2 multiple-texts comprehension than L2 single-text comprehension.